Collaborative creative thought and practice in music - Barrett, Margaret S. (SEMPRE studies in the psychology of music., 2014)
Focusing on the domain of music, the approach taken in this book falls into three sections: investigations of the people, processes, products, and places of collaborative creativity in compositional thought and practice; explorations of the ways in which creative collaboration provides a means of crossing boundaries between disciplines such as music performance and musicology; and studies of the emergence of creative thought and practice in educational contexts including that of the composer and the classroom. The volume concludes with an extended chapter that reflects on the ways in which the.